Outsourcing Failure and Reintegration: the influence of contractual and external factors - Cabral, Sandro (2013)
This paper discusses the reasons that drive organizations to interrupt outsourcing, reverse their previous decision, and then reintegrate activities formerly delegated to providers. Contractual approaches, mainly derived from Transaction Costs Economics, offer some plausible explanations for reintegration originating from outsourcing failure. These explanations are mainly related to asset specificity, poor contractual design, and deficient monitoring. The study of a real case of outsourcing interruption in industrial maintenance illustrates these different factors. However, some other determinants might complement the contractual and strategic background, namely bandwagon behavior and institutional pressure exerted by external actors. Finally, we propose an integrative framework that combines micro- and macro- levels of organizational analysis. We argue that some existing complementarities between the different theories we use here can shed some light on real organizational problems. Besides the implications for theory, our work can help managers to understand the dynamics of organizational boundaries, thus allowing them to make better choices in both outsourcing and reintegration decisions.